ANALISIS PENERAPAN STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL DALAM PENYAJIAN LAPORAN KEUANGAN DINAS LINGKUNGAN HIDUP KOTA SAMARINDA TAHUN 2017 - Dwi Joko Prabowo, Elfreda Aplonia Lau, dan Umi Kulsum (Prodi Ilmu Administrasi Negara, 2020)
The goal of the study to determine and analyze the presentation of : balance sheet, budget realization report, operational report, equity change report and notes on Samarinda City Environment Department's 2017 financial report and analyzing its compliance with Accrual Based Government Accounting Standards based on PP No.71 of 2010. Data collection techniques used in this study were interviews, documentation and observation. The analysis technique used is this study is comparative descriptive and presentation according to Jean D. Champion. The results of the study show that: First, the Balance Sheet presented at the Samarinda City Environment Agency is in the category of very in accordance with PP Number 71 Year 2010. Second, the Budget Realization Report presented at the Samarinda City Environmental Service is in the category very much in accordance with PP Number 71 of 2010. The third Operational Reports presented at the Samarinda City Environmental Agency are categorized according to Government Regulation Number 71 of 2010. Fourth, the Equity Change Report presented at the Samarinda City Environmental Office falls into the category of Government Regulation No. 71 Fifth, 2010. Presentation of posts presented in the Notes to the Financial Statements at the City of Samarinda Environmental Office is in the category of very in accordance with Government Accounting Standards based on PP No.71 of 2010.